PETROLEUM RESOURCE GOVERNANCE CRISIS AND THE DECLINE OF EDUCATION SECTOR IN NIGERIA 2015-2023 - Ajachukwu, Chinwendu Francis; Nwobashi, Humphrey Nwefuru (EBSU Journal of Social Sciences and Humanities, 2024)
The extent to which a government can develop its country depends on factors such as good governance, competence, accountability, availability of funds and educated citizens. Thus, the developed countries are able to enjoy quality education, good health services, economic opportunities and modern infrastructure. Unlike their counterparts in the developing countries, most of the people in developing countries such as Africa, Asia, and Latin America are plagued with the effects of underdevelopment which manifest as poverty, poor education, dilapidated infrastructure etc. Nigeria is among the countries that are still struggling to develop. Therefore, this work sought to interrogate Petroleum resource governance crisis and the decline of education sector in Nigeria with focus on its effects on education in Nigeria from 2015 to 2023.The study adopted explanatory research design, secondary sources of data collection which were obtained from reliable sources and analyzed to explain the phenomenon under investigation. The study is anchored on the resource curse theory as the theoretical framework of analysis. The study concluded that the maladministration of petroleum in Nigeria constitute to the decline in the development of the education sector. The study recommended amongst others that the Nigerian state should curb the corruption, properly administer and harness her petroleum sector to engender development in the education sector. This can be done by building refineries and diversifying the economy from petroleum dependence., the Nigerian state should increasingly fund education by increasing the annual budgetary provisions meant for education and ensure that the funds earmarked for education are adequately appropriated.